2020
DOI: 10.1186/s40945-020-00085-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative exercise in patients undergoing total knee arthroplasty: a pilot randomized controlled trial

Abstract: Background The purpose of this study was to assess the effect of preoperative physiotherapy (PT) on functional, subjective and socio-economic parameters after total knee arthroplasty (TKA). Methods 20 patients (mean ± SD: age 67 ± 7 years) scheduled for TKA at Balgrist University Hospital between July 2016 and March 2017 were randomly assigned to a control (CG) or intervention (IG) group. 3 to 4 weeks prior to surgery the IG completed 5 to 9 sessions of PT containing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…No matter which rehabilitation program can improve the postoperative function of knee surgery, so that patients get the best rehabilitation effect [ 6 ]. Preoperative training was reported as an effective and safe method to improve postoperative functional performance and muscle strength for patients having received TKA [ 7 ]. According to Calatayud et al [ 8 ] high-intensity preoperative supervised training can reduce postoperative pain, improve lower limb muscle strength, range of motion, and shorten the length of hospital stay in patients with TKA.…”
Section: Introductionmentioning
confidence: 99%
“…No matter which rehabilitation program can improve the postoperative function of knee surgery, so that patients get the best rehabilitation effect [ 6 ]. Preoperative training was reported as an effective and safe method to improve postoperative functional performance and muscle strength for patients having received TKA [ 7 ]. According to Calatayud et al [ 8 ] high-intensity preoperative supervised training can reduce postoperative pain, improve lower limb muscle strength, range of motion, and shorten the length of hospital stay in patients with TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies reported range of movement (Beaupre et al., 2004; Calatayud et al., 2017; Evgeniadis et al., 2008; Gränicher et al., 2020; Huang et al., 2012; Mat Eil Ismail et al., 2016; Matassi et al., 2014).…”
Section: Summary Of Interventionsmentioning
confidence: 99%
“…Thus, the policymakers, experimenters, and clinicians are still performing research studies for better ways to enhance the duration of recovery for the patients going through the total joint replacement. The total knee arthroplasty (TKA) is a voluntary surgical approach post the failure of conventional administration among the patients going through the improved knee osteoarthritis (KOA) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%